Tumor-Activated and Metal–Organic Framework Assisted Self-Assembly of Organic Photosensitizers - Wang, Yuanbo; Shi, Leilei; Ma, Dou; Xu, Shidang; Wu, Wenbo; Xu, Li; Panahandeh-Fard, Majid; Zhu, Xinyuan; Wang, Bo; Liu, Bin (ACS nano, 2020)
Tumor accumulation and intratumoral singlet oxygen (1O2) generation efficiency of photosensitizers (PSs) are two essential factors that determine their photodynamic therapy (PDT) efficacies. How to maximize the PS performance at the tumor site is of great research interest. Herein, we report a metal–organic framework (ZIF-8, ZIF = zeolitic imidazolate framework) assisted in vivo self-assembly nanoplatform, ZIF-8-PMMA-S-S-mPEG, as an effective tool for organic PS payloads to achieve efficient PDT. Using an organic PS with aggregation-induced emission as an example, under intratumoral bioreduction, PS-loaded ZIF-8-PMMA-S-S-mPEG (PS@ZIF-8-PMMA-S-S-mPEG) was self-assembled into large ordered hydrophobic clusters, which greatly enhance tumor retention and accumulation of the PS. Moreover, hydrophobic ZIF-8 assemblies greatly isolate the loaded PSs from water and improve O2 transport for the PSs to effectively produce 1O2 inside tumors under light irradiation. The organic PS is therefore endowed with optimal tumor accumulation and intratumoral 1O2 production, demonstrating the effectiveness of the developed self-assembly strategy in PDT application.